Chronic periodontitis and reduced respiratory function. (27th February 2019) - Winning, Lewis; Patterson, Christopher C.; Cullen, Kathy M.; Kee, Frank; Linden, Gerard J.
Abstract: Objective: To investigate whether there was an association between chronic periodontitis (CP) and reduced respiratory function. Methods: A group of dentate 58‐ to 72‐year‐old men in Northern Ireland had a comprehensive periodontal examination. Parallel to the periodontal examination, participants completed questionnaires gathering information on their medical history, social circumstances, demographic background and tobacco use. A physical examination assessed anthropometric measures. Fasting blood samples were obtained and analysed for high‐sensitivity C‐reactive protein (hs‐CRP). Spirometry measures were performed using a wedge bellows spirometer (Vitalograph S Model). The primary outcome variable of interest was the percentage predicted forced expiratory volume in one‐second (% predicted FEV1 ). Analysis included multiple linear regression with adjustment for various confounders and a regression‐based mediation analysis. Results: A total of 1, 380 men were included in the analysis. The mean age was 63.7 years ( SD 3.0). Multiple linear regression analysis showed that a doubling in mean clinical attachment loss (CAL) equated to a −3.33% (95% CI: −4.80, −1.86), p  <   0.001 change in % predicted FEV1 after adjustment for all other potential confounding variables. Systemic inflammation, as measured by hs‐CRP, only accounted for a minor mediating pathway effect (9%). Conclusions: In this homogenous group of dentate men, CP was significantly associated with a reduced respiratory function.